Republic of Mozambique : Fourth Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Mozambique. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Republic of Mozambique's Fourth Review Under the Policy Support Instrument (PSI) and Request for Modification of Assessment Criteria. Although program performance at end-2014 was mixed, the implementation of the structural reform agenda has improved, and the new government has expressed strong commitment to program implementation, including through strong policy adjustment, credible corrective measures, and new steps to improve fiscal transparency. Maintaining fiscal discipline over the medium term through a more prudent debt management strategy will be essential to preserve debt sustainability. The IMF staff recommends the completion of the fourth PSI review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet